RANCANGAN DASAR GASIFIER BATUBARA SIRKULASI UNGGUN MENGAMBANG UNTUK MEMBANGKITKAN LISTRIK 1 MW - Rahardjo, Bambang Suwondo; Sutrisna, I Putu (Jurnal Sains dan Teknologi Indonesia, 2007)
There are 3 choices in accommodating power station facility which have been installed to fulfill standard regulation of environmental quality which progressively tighten. Firstly, facility modification of pulverized–coal fired power plant by applying a flue–gas desulfurisation technology throw away to cost money installation of tired which can 20% of total cost development of it. Secondly, modification system of coal fired power generation become natural gas combined cycle (NGCC) can reach low emission, but fuel cost relatively high, so will influence the electricity generating cost. Third, modification system of electric generation which have been installed by utilizing a mechanism of coal gasification is most efficient and best alternative to yield an environmental friendly of electric generation combined cycle. In this paper, writer try to make a basic design of circulating fluidized–bed coal gasifier using clay catalist related on third choice which expected applicable in the next future to come replace power station system which have ended a period as well as newly even if.